Calcium and electrical signaling in arterial endothelial tubes: New insights into cellular physiology and cardiovascular function. (April 2017) - Behringer, Erik J.
Abstract: The integral role of the endothelium during the coordination of blood flow throughout vascular resistance networks has been recognized for several decades now. Early examination of the distinct anatomy and physiology of the endothelium as a signaling conduit along the vascular wall has prompted development and application of an intact endothelial "tube" study model isolated from rodent skeletal muscle resistance arteries. Vasodilatory signals such as increased endothelial cell (EC) Ca 2+ ([Ca 2+ ]i ) and hyperpolarization take place in single ECs while shared between electrically coupled ECs through gap junctions up to distances of millimeters (≥2 mm). The small‐ and intermediate‐conductance Ca 2+ activated K + (SKC a /IKC a or KC a 2.3/KC a 3.1) channels function at the interface of Ca 2+ signaling and hyperpolarization; a bidirectional relationship whereby increases in [Ca 2+ ]i activate SKC a /IKC a channels to produce hyperpolarization and vice versa . Further, the spatial domain of hyperpolarization among electrically coupled ECs can be finely tuned via incremental modulation of SKC a /IKC a channels to balance the strength of local and conducted electrical signals underlying vasomotor activity. Multifunctional properties of the voltage‐insensitive SKC a /IKC a channels of resistance artery endothelium may be employed for therapy during the aging process and development of vascular disease.